Transformation of Business Process Models: A Case Study - Linda Anthuanett Norabuena Padilla (2014)
Model-Driven Architecture (MDA) is a visionary approach in software development. This approach is investigated by a broad community of researchers and companies which increasingly consider it a potentially interesting area. In software engineering, MDA provides great advantages in order to reduce the effort required to implement systems, reuse predefined resources and mainly provide an intuitive way to address the complexity that the definition of a system requires. However, there are still challenges that affect the efficiency and the context of the applicability of the method. In a business environment, to apply MDA practices are means to achieve quality and flexibility in the solutions that organizations provide to their customers. The tendency to put into practice the methodologies of MDA has attracted the interest of organizations in the information technology industry. Sysnovare Solution Innovation SA is a concrete example of this trend; thus, Sysnovare presents a case study of its innovative products in the management of business processes e.g. the Business Process Management Suite, also known as BPM suite. The project challenge is born with the purpose of defining a mechanism of integration between BPM suite and a process modeling tool. The integration of these tools will permit the interoperability of the suite to evolve, contributing not only to the performance of the phases of modeling a business process, but also to the monitoring phase. Both systems incorporating the solution conform to a particular data structure. The effort to transform a model that is generated by the suite into a model that is generated by the graphical tool will be the basis for the development of the project. To establish a communication mechanism it was essential to specify in advance the modeling tool and data that are shared in communication. The graphics engine mxGraph is a framework integrated in the BPM suite. This technology allows implementing a flexible modeling tool, which is adaptable to the needs of the suite. An adapted version of Draw.io application, built on the basis of the graphics engine, will be the tool to model business processes in a suitable standard notation. With regard to transformation of models, two template levels define the system. The layer of input and output data processing is developed with the transformation language XSLT; the language will be used to define transformation rules that may undergo fewer changes in the evolution of the tool. QVT-R, on the contrary, will be used in the second level models with the goal of mapping the basic elements and modelling a business process. Finally, modeling tools are used to build the model transformation tool; thus, the approach leverages technologies such as Medini QVT and Eclipse Modeling (EMF) to test the applicability of the approach: In response to the challenge of Sysnovare, the two parts of the research and analysis are important to specify the external interoperability of BPM suite. Implementing MDA methodologies in BPM suite contributes to the research community by presenting a case study of the implementation of the practices of MDA in the transformation of business models.